OH DEFECTS IN CASSITERITE - Losos Z.; Beran A. (My University, 2004)
Two infrared (IR) spectral types are discerned in cassiterites with OH defect concentrations ranging from several wt. ppm H2O in synthetic melt-grown samples up to 0.017 wt.% in natural samples of hydrothermal origin. Spectrum type I is characterised by one sharp band centred at 3255 cm-1, type II spectra reveal an additional band group centred around 3340 cm-1, which is clearly correlated with the presence of Ti. Both OH band groups are strongly polarised with maximum absorption perpendicular to the c-axis. Type I spectra prevail in nearly colourless samples, type II spectra typically occur in light to dark brown cassiterites, bearing essentially higher amounts of minor elements, especially Ti, Nb, Ta, W, Zr, and Fe. The total amount of water is not significantly correlated with the minor element content. It is concluded that different OH concentrations reflect different water activities prevalent during the formation of cassiterite crystals in different geological environments.
Keywords: cassiterite